PENGARUH PEMBERIAN PUPUK CAIR DAUN KELOR DAN CANGKANG TELUR TERHADAP PERTUMBUHAN SAWI SAMHONG (Brassica juncea L.) - arum asriyanti suhastyo; Fanny Tri Raditya (Jurnal AGROSAINS dan TEKNOLOGI, 2021)
Growth in mustard greens is greatly influenced by the availability of macro nutrients and micro nutrients, where if the availability of nutrients in the soil is not optimal, fertilization must be carried out. This study aims to examine the effect of the application of liquid organic fertilizer, moringa leaves and eggshells with different concentrations and intervals of fertilizer on the growth of mustard greens. The research design used was a factorial Randomized Block Design, with two factors being tried namely fertilizer application and fertilizer time intervals. First factor: without administration of POC (K0), Moringa leaf POC: eggshell POC 25: 75 ml / l (K1), Moringa leaf POC: eggshell POC 50: 50 ml / l (K2), moringa leaf POC: eggshell POC eggs 75: 25 ml / l (K3). The second factor: the interval of giving F1 fertilizer = 5 days, F2 = 6 days, F3 = 7 days. Each treatment was repeated 3 times to obtain 36 experimental plots. Analysis of the data used to determine the observed response to the treatment given was done by the Analysis of Variance Analysis (ANOVA) and if it showed a real difference followed by Duncan's Multiple Range Test. The conclusion of this study shows that the application of Daunkelor liquid fertilizers and eggshell to the growth of mustard Samhong has not been able to increase plant height, number of leaves and fresh weight of the plan